New synonyms and lectotypifications in Brazilian Erythroxylum (Erythroxylaceae) - Costa-Lima, James Lucas; Loiola, Maria Iracema Bezerra; Alves, Marccus (Phytotaxa, 2015)
Erythroxylum Browne (1756: 278) includes about 230–240 species and is the only genus of Erythroxylaceae Kunth (1821: 175) occurring in the Neotropical region (Plowman & Berry 1999, Plowman & Hensold 2004). The eastern and northeastern Brazil and Venezuela are considered centers of its diversity and endemism (Daly 2004). For Brazil, 123 species are recognized, with the greatest species richness in the Atlantic Forest Domain, especially in its northeastern region, where 46 species have been reported, with 17 of them endemic (Loiola & Costa-Lima 2014).